In silico methods in prediction of drug metabolism, mass fragmentation, and chromatographic behavior : application to toxicological drug screening by liquid chromatography/time-of-flight mass spectrometry - Tyrkkö, Elli (University of Helsinki, 2014)
Tiivistelmä suomeksi.
Keywords: lääkeaineet; huumeet; tunnistaminen; aineenvaihdunta; toksikologia; kromatografia; massaspektrometria; simulointi; tietokoneavusteisuus